Baker topical guide to the Bible - Elwell, Walter A.; Buckwalter, Douglas (Grand Rapids, MI Baker, 2000)
Includes indexes.
Originally published as "Topical analysis of the Bible" in 1991. Contents unchanged.
Keywords: Doctrine (theology) -- themes